A Second 5-Carboxyvanillate Decarboxylase Gene, ligW2, Is Important for Lignin-Related Biphenyl Catabolism in Sphingomonas paucimobilis SYK-6 - Peng, Xue (American Society for Microbiology, 2005)
A lignin-related biphenyl compound, 5,5′-dehydrodivanillate (DDVA), is degraded to 5-carboxyvanillate (5CVA) by the enzyme reactions catalyzed by DDVA O-demethylase (LigX), meta-cleavage oxygenase (LigZ), and meta-cleavage compound hydrolase (LigY) in Sphingomonas paucimobilis SYK-6. 5CVA is then transformed to vanillate by a nonoxidative 5CVA decarboxylase and is further degraded through the protocatechuate 4,5-cleavage pathway. A 5CVA decarboxylase gene, ligW, was isolated from SYK-6 (X. Peng, E. Masai, H. Kitayama, K. Harada, Y, Katayama, and M. Fukuda, Appl. Environ. Microbiol. 68:4407-4415, 2002). However, disruption of ligW slightly affected the 5CVA decarboxylase activity and the growth rate on DDVA of the mutant, suggesting the presence of an alternative 5CVA decarboxylase gene. Here we isolated a second 5CVA decarboxylase gene, ligW2, which consists of a 1,050-bp open reading frame encoding a polypeptide with a molecular mass of 39,379 Da. The deduced amino acid sequence encoded by ligW2 exhibits 37% identity with the sequence encoded by ligW. Based on a gas chromatography-mass spectrometry analysis of the reaction product from 5CVA catalyzed by LigW2 in the presence of deuterium oxide, LigW2 was indicated to be a nonoxidative decarboxylase of 5CVA, like LigW. After disruption of ligW2, both the growth rate on DDVA and the 5CVA decarboxylase activity of the mutant were decreased to approximately 30% of the wild-type levels. The ligW ligW2 double mutant lost both the ability to grow on DDVA and the 5CVA decarboxylase activity. These results indicate that both ligW and ligW2 contribute to 5CVA degradation, although ligW2 plays the more important role in the growth of SYK-6 cells on DDVA.